2017
DOI: 10.1016/j.bbagrm.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of nucleotide entry into RNA polymerase active site provides mechanism for efficiency and fidelity

Abstract: During transcription, RNA polymerase II elongates RNA by adding nucleotide triphosphates (NTPs) complementary to a DNA template. Structural studies have suggested that NTPs enter and exit the active site via the narrow secondary pore but details have remained unclear. A kinetic model is presented that integrates molecular dynamics simulations with experimental data. Previous simulations of trigger loop dynamics and the dynamics of matched and mismatched NTPs in and near the active site were combined with new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Following transition to MR20, simulations aMD_L1 and L2 sample bind to i + 1. Strikingly, no E site coordination [ 3 , 5 , 8 , 10 ] was observed; the incoming NTP bound directly to the i + 1 register without undergoing the preliminary inverted coordination to the metal binding sites ( 1 D495, 1 D497, 1 D499, 2 E791, and 2 D792). Instead, we observed only a partial interaction with the metal site preceding binding to i + 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following transition to MR20, simulations aMD_L1 and L2 sample bind to i + 1. Strikingly, no E site coordination [ 3 , 5 , 8 , 10 ] was observed; the incoming NTP bound directly to the i + 1 register without undergoing the preliminary inverted coordination to the metal binding sites ( 1 D495, 1 D497, 1 D499, 2 E791, and 2 D792). Instead, we observed only a partial interaction with the metal site preceding binding to i + 1.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of an entry site (E site), which is able to bind nucleotides in the corridor, suggests CH2 as the most obvious access point to this location [ 3 , 4 , 5 , 6 , 7 , 8 ]. Molecular dynamics (MD) simulations of NTP diffusion substantiate that CH2 is compatible with the observed in vivo synthesis rate [ 9 , 10 ], whereas alternative pathways do not appear to satisfy conformational and electrostatic requirements for NTP loading [ 11 ]. Finally, the CH2 model correlates well to the more general nucleotide addition cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Of the five kinetic checkpoints proposed by Feig et al for multi‐subunit RNA Pols, two occur prior to the chemical step: (1) rotation of the NTP as it moves from the entry site to the insertion site and (2) steric interaction between the closed trigger loop and NTP 163 . It was subsequently demonstrated that a kinetic model including these checkpoints could reproduce the experimental misincorporation rate 164 . On the other hand, for the viral single‐subunit T7 RNA Pol, Yu et al proposed three prechemistry kinetic checkpoints: (1) NTP dissociation from the preinsertion site, (2) NTP binding at the insertion site, and (3) NTP dissociation from the insertion site (i.e., the reverse of 2) 165,166 .…”
Section: Computational Studies Of Polymerase Catalytic Mechanism and Propertiesmentioning
confidence: 99%
“…Markov State Model (MSM) is a popular method that can bridge this timescale gap (32)(33)(34)(35)(36)(37)(38)(39)(40)(41), in which continuous dynamics are modeled as Markovian transitions among metastable conformational states at discrete time intervals (lag times). MSMs have been widely applied to study protein conformational changes (40,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), including those involved in the elongation of multisubunit RNAP (44,55,(57)(58)(59)(60)(61)(62). MSMs must be constructed with long enough lag times to allow Markovian interstate transitions.…”
Section: Significancementioning
confidence: 99%